THE ROLE OF ISLAMIC BOARDING SCHOOLS IN PREVENTING RADICALISM - Dewi Evi Anita; Roshifah Jauhari (Pascasarjana Universitas Wahid hasyim Semarang, 2025)
The phenomenon of radicalism in Indonesia is a serious challenge to the integrity of the nation. Traditional Islamic educational institutions such as Islamic Boarding Schools have a strategic role in counteracting the spread of radicalism. This study aims to examine the role of Islamic Boarding Schools in preventing radicalism through a descriptive qualitative approach. The results of the study show that Islamic Boarding Schools with an Islamic moderation-based curriculum, exemplary kiai, as well as cultural and spiritual approaches are able to become effective ideological fortresses. The role of Islamic Boarding Schools is not only as educational institutions, but also as agents of peace and guardians of national values. This study recommends strengthening the synergy between the government and Islamic Boarding Schools in building a peaceful and inclusive Islamic narrative.